2018
DOI: 10.1101/449793
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling cellular response in large-scale radiogenomic databases to advance precision radiotherapy

Abstract: Radiotherapy is integral to the care of a majority of cancer patients. Despite differences in tumor responses to radiation (radioresponse), dose prescriptions are not currently tailored to individual patients. Recent large-scale cancer cell line databases hold the promise of unravelling the complex molecular arrangements underlying cellular response to radiation, which is critical to novel predictive biomarker discovery. Here, we present RadioGx, a computational platform for integrative analyses of radiorespon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Breast cancer. The AR has been shown to be a potential mediator of radioresistance and a target for the radiosensitization of AR+ TNBC [100][101][102]200 . Inhibition of AR with enzalutamide results in increased radiosensitization of AR+ breast cancer cells through the inhibition of AR-activated DNA-PKcs-mediated repair 100 .…”
Section: Combination Therapies Ar + Radiation Therapymentioning
confidence: 99%
“…Breast cancer. The AR has been shown to be a potential mediator of radioresistance and a target for the radiosensitization of AR+ TNBC [100][101][102]200 . Inhibition of AR with enzalutamide results in increased radiosensitization of AR+ breast cancer cells through the inhibition of AR-activated DNA-PKcs-mediated repair 100 .…”
Section: Combination Therapies Ar + Radiation Therapymentioning
confidence: 99%
“…We hope and envision that this package will help users to compare their own signature to those in the RadiationGeneSigDB database, and help build better biomarkers by using multiple datasets in the discovery, or pre-clinical phase. Furthermore, RadiationGeneSigDB coupled with RadioGx, a novel computational platform of radiogenomics datasets (Manem et al , 2018) , will enable us to build reliable and clinically-verifiable genomic predictors of radiation response.…”
Section: Resultsmentioning
confidence: 99%
“…Intratumoral genomic heterogeneity in GBM has limited the efficacy of personalized targeted therapies. To overcome this barrier, we sought to discover 16 metabolic pathways that caused RT-resistance in GBM independently of genotype. By analyzing how intracellular metabolite levels correlated with GBM RT resistance, we found that low levels of nucleobase-containing metabolites were strongly associated with sensitivity to RT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, efforts to overcome primary RT-resistance are likely to improve outcomes in patients with GBM. Efforts to develop new strategies to overcome RT-resistance have previously used large-scale genomic profiling data to define candidate oncogenic molecular alterations to target in combination with radiation 14,15,16 . Due to the profound genomic heterogeneity of GBM, we instead sought to define therapeutic strategies that could overcome RT-resistance independently of genotype.…”
Section: Introductionmentioning
confidence: 99%